Adjustment of the GRACE score by the stress hyperglycemia ratio improves the prediction of long-term major adverse cardiac events in patients with acute coronary syndrome undergoing percutaneous coronary intervention: A multicenter retrospective study. (April 2023) - Xiong, Shiqiang; Luo, Yan; Chen, Qiang; Chen, Yingzhong; Su, Hong; Long, Yu; Chen, Xu; Yang, Siqi; Qi, Lingyao; Huang, Wenchao; Hou, Jun; Liu, Hanxiong; et al.
Abstract: Aims: The predictive value of the stress hyperglycemia ratio (SHR) for long-term prognosis in acute coronary syndrome (ACS) is inconsistent. Whether the SHR provides additional prognostic value in addition to the GRACE score in ACS patients undergoing percutaneous coronary intervention (PCI) remains unknown. Methods: A development–validation method was adopted to develop an algorithm to adjust the GRACE score using the SHR in ACS patients undergoing PCI from 11 hospitals. Results: During a median follow-up of 31.33 months, the occurrence of major adverse cardiac events (MACEs), defined as a composite of all-cause mortality and nonfatal myocardial infarction, was more frequent in the patients with a higher level of SHR. The SHR independently predicted long-term MACEs (hazard ratio 3.3479; 95% CI 1.4103–7.9475; P = 0.0062). Adjustment of the GRACE risk by addition of the SHR increased the C-statistic from 0.706 (95% CI: 0.599–0.813) to 0.727 (95% CI: 0.616–0.837) (P < 0.01), with a continuous net reclassification improvement of 30.5% and an integrated discrimination improvement of 0.042 (P < 0.01) in the derivation cohort; and addition of the SHR showed superior discrimination and good calibration in the validation cohort. Conclusions: The SHR is an independent predictor of long-term MACEs in ACS patients undergoing PCI and markedly improves the performance of the GRACE score.